M06 Olesoxime Treatment Inhibits The Formation Of Mhtt Fragments Through Suppression Of Calpain Activity, And Leads To Behavioural And Neurological Improvements In The Bachd Rat. (17th September 2014) - Clemens, LE; Weber, JJ; Wlodkowski, TT; Yu-Taeger, L; Michaud, M; Magg, JCD; Casadei, NL; Calaminus, C; Eckert, S; Eckmann, J; Weiss, A; Eckert, G; et al.
Abstract : Background: Proteolytic cleavage of the mutant huntingtin protein (mHtt) leads to toxic N-terminal mHtt fragments, which are known to disrupt mitochondrial function. Olesoxime, a small cholesterol-like molecule, targets mitochondria and has demonstrated therapeutic efficacy in a variety of disease models. Recent clinical investigations revealed exciting results in spinal muscular atrophy patients, where olesoxime was found to be the first drug to efficiently block the progression of motor deficits in a clinical type II study. Furthermore, it was found to increase the survival of primary striatal neurons overexpressing mHtt, suggesting therapeutic potential also for HD. Aims: To evaluate the therapeutic potential of olesoxime in the BACHD rat model of HD. Methods: Olesoxime was supplied to BACHD rats via drug-loaded food pellets from the age of 5 weeks on, and the rats' behaviour was studied for 12 months. Brain atrophy was investigated with MRI at 13 months. Mitochondrial parameters, mHtt cleavage and aggregation were measured in brain lysates ex vivo . Results: We found olesoxime to specifically ameliorate psychiatric and cognitive disturbances of BACHD rats, to increase frontal cortex thickness and to improve mitochondrial function. Very interestingly, the beneficial effects seemed to be mediated by a downregulation of calpain activity, thereby drastically reducing the formation of mHtt fragments and aggregates, and increasing soluble mHtt levels. Conclusions: Our study reveals new insights into olesoxime's mechanism of action and highlights olesoxime as a novel tool for reducing toxic mHtt fragments.